EDUKASI MEDIA KARTU BERGAMBAR BERPENGARUH TERHADAP PENGETAHUAN DAN SIKAP ANAK DALAM PEMILIHAN JAJANAN SEHAT DI SD NEGERI PONTIANAK UTARA - Pina Septiana; Suaebah Suaebah (Pontianak Nutrition Journal (PNJ), 2018)
Street food becomes the most concerned thing that eaten by most of children in the school. The consumption of snack cannot be separated from the danger of the negative impact. It is the proves that education about selecting healthy street food should be given. The purpose of this study to determine the effect of educational visual media with picture card method on knowledge and attitudes of children in the selection of healthy street food. The method used is Quasy-Experiment research study design by pretest-posttest with control group design is to see their influence on the treatment and control groups with measurements before and after treatment using the Wilcoxon test and Mann-Whitney test with a significance level of = 0.05. The results showed that there was a significant increase in knowledge (p = 0.000) and attitude (p = 0,000) of children in the selection of healthy street food. The conclusion of this study is educational influence of visual media with picture card method before and after the intervention of the knowledge and attitudes of children in the selection of healthy street food.